Homogenization of nonaging basic creep of cementitious materials: A multiscale modeling benchmark. (5th July 2021) - Königsberger, Markus; Honório, Túlio; Sanahuja, Julien; Delsaute, Brice; Pichler, Bernhard L.A.
Highlights: Three micromechanics creep models are applied in a modeling benchmark. Macroscopic creep results from intrinsic creep of microscopic C-S-H. Considering non-spherical shapes for C-S-H hydrates improves model performance. Separating instantaneous from time-dependent strains in experiments is essential. Abstract: This paper presents the results of a European benchmark on multiscale creep modeling for cementitious materials, performed in the framework of the COST Action TU1404 "Towards the next generation of standards for service life of cement-based materials and structures". Three micromechanical models from three research groups have been adopted for modeling the basic non-aging creep of cementitious materials. The benchmark is based on the hypotheses that creep results only from calcium-silicate-hydrates (C-S-H) and that viscoelastic behavior of all microstructural constituents is maturity- and composition-independent. By comparing model results among themselves as well as by comparing model predictions with experimental results obtained from three different laboratories, we demonstrate that creep upscaling from micrometer-sized C-S-H to centimeter-sized macroscopic samples of cement paste, mortar, and concrete, and from minutes-long creep tests at early ages to days-long creep tests at very mature ages is indeed possible. The benchmark also highlights the importance of considering micro-anisotropy of C-S-H in terms of non-spherical shapes for C-S-H hydrates.